A collection of barcoded natural isolates of Saccharomyces paradoxus to study microbial evolutionary ecology. Issue 7 (19th December 2018) - Bleuven, Clara; Dubé, Alexandre K.; Nguyen, Guillaume Q.; Gagnon‐Arsenault, Isabelle; Martin, Hélène; Landry, Christian R.
Abstract: While the use of barcoded collections of laboratory microorganisms and the development of barcode‐based cell tracking are rapidly developing in genetics and genomics research, tools to track natural populations are still lacking. The yeast Saccharomyces paradoxus is an emergent microbial model in ecology and evolution. More than five allopatric and sympatric lineages have been identified and hundreds of strains have been isolated for this species, allowing to assess the impact of natural diversity on complex traits. We constructed a collection of 550 barcoded and traceable strains of S. paradoxus, including all three North American lineages SpB, SpC, and SpC* . These strains are diploid, many have their genome fully sequenced and are barcoded with a unique 20 bp sequence that allows their identification and quantification. This yeast collection is functional for competitive experiments in pools as the barcodes allow to measure each lineage's and individual strains' fitness in common conditions. We used this tool to demonstrate that in the tested conditions, there are extensive genotype‐by‐environment interactions for fitness among S. paradoxus strains, which reveals complex evolutionary potential in variable environments. This barcoded collection provides a valuable resource for ecological genomics studies that will allow gaining a better understanding of S. paradoxus evolution and fitness‐related traits. Abstract : This study presents a collection of 550 barcoded and traceable strains of S. paradoxus, functional for competitive experiments in pools. This collection provides a valuable resource for ecological genomics studies that will allow gaining a better understanding of S. paradoxus evolution and fitness‐related traits.